Reactivity of tetrahydrochromeno[2, 3‐b]indoles: chromic indicators of cyanide. (25th June 2013) - Douglas, Nicholas; Neef, Charles J.; Rogers, Robert A.; Stanley, Jake A.; Armitage, Jacob; Martin, Ben; Hudnall, Todd W.; Brittain, William J.
<x xml:space="preserve">Abstract</x> The synthesis and reactivity of a tetrahydrochromeno[2, 3‐b]indoles are reported. Evidence for reversible ring‐opening is based on H/D exchange and trapping experiments. These compounds readily undergo reaction with tetra‐n‐butylammonium cyanide. The cyanide reaction is 10–100× faster when the solution is irradiated with 350 nm light. Reaction with trimethylsilyl cyanide occurs only with UV irradiation demonstrating photoreactivity. The rate of tetrahydrochromeno[2, 3‐b]indole ring‐opening is greater for (i) Me substitution at the hemiaminal carbon (compared to Ph), and (ii) substitution of fluorine at the 9‐position of the indole. Under acidic conditions, the ring‐opened indolium ion is observed. Copyright © 2013 John Wiley & Sons, Ltd.